2020
DOI: 10.1016/j.cortex.2020.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Altered phobic reactions in frontotemporal dementia: A behavioural and neuroanatomical analysis

Abstract: Introduction Abnormal behavioural and physiological reactivity to emotional stimuli is a hallmark of frontotemporal dementia (FTD), particularly the behavioural variant (bvFTD). As part of this repertoire, altered phobic responses have been reported in some patients with FTD but are poorly characterised. Methods We collected data (based on caregiver reports) concerning the prevalence and nature of any behavioural changes related to specific phobias in a cohort of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Changes in sensory behaviour (Bathgate et al, 2001; Fletcher et al, 2015) include reduced responsiveness to pain, which may lead to injury and burns, exaggerated response to innocuous stimuli such as light touch and altered response to heat and cold. Hypochondriasis (Snowden et al, 1996) and phobic responses (Jimenez et al, 2020) may occur.…”
Section: Behavioural and Cognitive Characteristics Of Bvftdmentioning
confidence: 99%
“…Changes in sensory behaviour (Bathgate et al, 2001; Fletcher et al, 2015) include reduced responsiveness to pain, which may lead to injury and burns, exaggerated response to innocuous stimuli such as light touch and altered response to heat and cold. Hypochondriasis (Snowden et al, 1996) and phobic responses (Jimenez et al, 2020) may occur.…”
Section: Behavioural and Cognitive Characteristics Of Bvftdmentioning
confidence: 99%
“…Firstly, there is strong genetic susceptibility to both PD and AD [14]. Secondly, observational studies have found that AD patients are often comorbid with PD, phobias, and even anxiety, and that the quality of life of patients with these comorbidities is severely affected [15][16][17]. In contrast, patients with PD scored worse in all cognitive areas, and they performed worse in memory tasks [18].…”
Section: Introductionmentioning
confidence: 99%